07 Defective mitochondrial mRNA maturation is associated with spastic ataxia. Issue 3 (15th February 2011) - Christos, Proukakis; Patel, H; Chioza, B A; Dick, K; Al-Memar, A; Chrzanowksa-Lightowlers, Z M A; Cross, H; Patton, M A; Lightowlers, R N; Crosby, A H
Abstract : Mitochondrial dysfunction, acquired or inherited, is important in several neurodegenerative disorders. Several causes of autosomal recessive ataxias are known. Investigation of a recessively inherited form of progressive spastic ataxia with optic atrophy present amongst the Old Order Amish in Ohio, USA, led to the identification of a homozygous mutation of MTPAP in affected individuals. This nuclear gene encodes the mitochondrial poly(A) RNA polymerase which is essential for maintaining mitochondrial gene expression by polyadenylation of mRNA. When subjected to poly(A) tail length assays, mitochondrial mRNAs from affected individuals were shown to have severely truncated mitochondrial poly(A) tails. Although defects in mitochondrial DNA are well characterised, these findings reveal the first defect of mitochondrial RNA maintenance associated with human disease, and imply that this disease mechanism should be considered in other complex neurodegenerative disorders.